ANALISIS PENGARUH REVALUASI ASET TETAP TERHADAP HARGA SAHAM PERUSAHAAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA - MIFTAHUL HUDA; YUNUS TETE KONDE; IRWANSYAH - (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
The aims of this research is to analys the effect of fixed asset revaluation on company share price by using simple regression model as the method. This research  uses time series data of annual report year 2015 and share price on 02 May year 2016 from Indonesian Stock Exchange. Purpossive judgment is used as sampling method wich result 30 company fulfill the criteria of the sample by revaluation of fixed asset activity in year 2015. The result of hypotesis testing indicates that fixed asset revaluation has a possitive effect on share price significantly. Finding of this research show support for Signalling Theory which  state that all of company activities about signalling is to rich public interest could increase the share price. The result of this research also support the Trade-off Theory of Capital Stucture which state that balancing debt and capital stucture can increase value of company and could increase the  share price.Keyword: Capital Structure, Fixed Asset Revaluation.